Characterization of the natural mineral form from the PbS-Sb2S3 system - Štrbac N.; Mihajlović I.; Minić D.; Živković Ž. (Journal of Mining and Metallurgy. Section B: Metallurgy)
This paper presents the results of experimental investigations of natural mineral form from the PbS - Sb2S3 system. Investigated sulfosalt appears in nature in the form of nanowires with diameters ranging from 200 to 500 nm and its length can reach up to 150 mm. In most cases these nanowires are arranged like bundles, which were inspected with scanning electron microscopy (SEM). The chemical composition of this material was analyzed and its stoichiometry responded to 'plumosite'. Crystal structure was analyzed using XRD analyses and compared to available literature data. Investigated samples were subjected to thermal analyses and resulting mechanism of oxidation was concluded. Also, kinetic parameters were calculated for the process of oxidation.